2023
DOI: 10.3389/fendo.2023.1236878
|View full text |Cite
|
Sign up to set email alerts
|

Autoimmune polyglandular syndrome type 4: experience from a single reference center

Elisa Gatta,
Valentina Anelli,
Elena Cimino
et al.

Abstract: PurposeTo characterize patients with APS type 4 among those affected by APS diagnosed and monitored at our local Reference Center for Autoimmune Polyglandular Syndromes.MethodsMonocentric observational retrospective study enrolling patients affected by APS diagnosed and monitored in a Reference Center. Clinical records were retrieved and analyzed.Results111 subjects (51 males) were affected by APS type 4, mean age at the onset was 23.1 ± 15.1 years. In 15 patients the diagnosis of APS was performed during the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 46 publications
(69 reference statements)
0
2
0
Order By: Relevance
“…Furthermore, a recent retrospective cohort study revealed a strong association between autoimmune thyroid diseases (Hashimoto’s and Grave’s diseases) and diminished ovarian reserve as well as POF ( 22 ). Other studies have also reported a 5% occurrence of POF in women with autoimmune polyglandular syndrome-4 (APS-4) ( 23 ). Additionally, autoimmune diseases such as Addison’s disease and systemic lupus erythematosus (SLE) pose a risk for POF, with SLE carrying a risk ranging from 0.6% to 43% ( 24 ).…”
Section: Discussionmentioning
confidence: 95%
“…Furthermore, a recent retrospective cohort study revealed a strong association between autoimmune thyroid diseases (Hashimoto’s and Grave’s diseases) and diminished ovarian reserve as well as POF ( 22 ). Other studies have also reported a 5% occurrence of POF in women with autoimmune polyglandular syndrome-4 (APS-4) ( 23 ). Additionally, autoimmune diseases such as Addison’s disease and systemic lupus erythematosus (SLE) pose a risk for POF, with SLE carrying a risk ranging from 0.6% to 43% ( 24 ).…”
Section: Discussionmentioning
confidence: 95%
“…Apart from a few cohort studies that have described the prevalence of CD in autoimmune polyglandular syndromes, to the best of our knowledge, no systematic assessments of APS prevalence in Italian CD adult patients have been reported so far [15][16][17].…”
Section: Discussionmentioning
confidence: 99%